Borage, calendula, cosmos, Johnny Jump up, and pansy flowers: volatiles, bioactive compounds, and sensory perception - Fernandes, Luana (2018)
The aim of the present work was to study the main volatile and bioactive compounds (monomeric anthocyanins, hydrolysable tannins, total flavonoids, and total reducing capacity) of five edible flowers: borage (Borage officinalis), calendula (Calendula arvensis), cosmos (Cosmos bipinnatus), Johnny Jump up (Viola tricolor), and pansies (Violaxwittrockiana), together with their sensory attributes. The sensory analysis (10 panelists) indicated different floral, fruity, and herbal odors and taste. From a total of 117 volatile compounds (SPME-GC-MS), esters were most abundant in borage, sesquiterpenes in calendula, and terpenes in cosmos, Johnny Jump up, and pansies. Some bioactive and volatile compounds influence the sensory perception. For example, the highest content of total monomeric anthocyanins (cosmos and pansies) was associated with the highest scores of colors intensity, while the floral and green fragrances detected in borage may be due to the presence of ethyl octanoate and 1-hexanol. Therefore, the presence of some volatiles and bioactive compounds affects the sensory perception of the flowers.